The Cambridge introduction to Literature and the Environment - Clark, Timothy (Timothy John Andrew) 1958- (Cambridge, UK Cambridge University Press, 2011)
"Environmental criticism is a relatively new discipline that brings the global problem of environmental crisis to the forefront of literary and cultural studies. This introduction defines what ecocriticism is and provides a set of conceptual tools to encourage students to look at the texts they're reading in a new way"--Provided by publisher.
"The degrading environment of the planet is something that touches everyone. This book offers an introductory overview of literary and cultural criticism that concerns environmental crisis in some form. Both as a way of reading texts and as a theoretical approach to culture more generally, 'ecocriticism' is a varied and fast-changing set of practices which challenges inherited thinking and practice in the reading of literature and culture. This introduction defines what ecocriticism is, its methods, arguments and concepts, and will enable students to look at texts in a wholly new way. Boxed sections explain key critical terms and contemporary debates in the field with 'hands-on' examples and comparisons. Timothy Clark's thoughtful approach makes this an ideal first encounter with environmental readings of literature"--Provided by publisher.
Machine generated contents note: Preface; Introduction: the challenge; Part I. Romantic and Anti-Romantic: 1. Old World Romanticism; 2. New World Romanticism; 3. Genre and the ethics of nonfiction; 4. Language beyond the human?; 5. The inherent violence of Western thought?; 6. Posthumanism and the 'end of nature'; Part II. The Boundaries of the Political: 7. Thinking like a mountain?; 8. Environmental justice and the move 'beyond nature writing'; 9. European eco-justice; 10. Liberalism and Green moralism; 11. Ecofeminism; 12. 'Postcolonial' eco-justice; 13. Questions of scale: the local, the national and the global; Part III. Science and the Struggle for Intellectual Authority: 14. Science and the crisis of authority; 15. Science studies; 16. Evolutionary theories of literature; 17. Interdisciplinarity and science: two essays on human evolution; Part IV. The Animal Mirror: 18. Ethics and the nonhuman animal; 19. Anthropomorphism; 20. The future of ecocriticism.
Includes bibliographical references and index.
Keywords: Ecocriticism; Nature in literature